Leather Craft Industry and Tourism: A Symbiotic Relationship? (A Case Study of Magetan East Java Indonesia) - Sugiarti, Rara; Margana, Margana; Muthmainah, Muthmainah; Fauzia, Laela Rizki (Department of Drama, Dance and Music, FBS, Universitas Negeri Semarang, 2019)
This article examines how leather craft industry contributes to tourism development in Magetan East Java Indonesia and vice versa. This study applied a qualitative approach and is descriptive in nature. Techniques of collecting data include site observation, interview, document review, and focus group discussion. Data were analyzed using the interactive model and thematic analysis. Research results indicate four themes. First, leather craft industry in Magetan that is mostly home industry has been empowered in many ways. Several aspects, including a high number of tourist visits, local government policy, abundant human resources, and industrious businessmen have strengthened the industry. Some local government policies have been implemented in several programs to develop the industry. Second, quality products and new design innovation for leather crafts are limited. Most products that are dominated by shoes and sandals are created for lower-middle-income consumers. Third, leather craft industries in Magetan have contributed to the establishment of local entrepreneurship, small-medium enterprises, and tourism. They create job opportunities for the locals and boost the local economy. Fourth, the relationship between leather craft centers and tourism activities is dominated by tourists’ purchase of leather craft products for souvenirs. However, tourism activity in the area is not yet aimed at watching and involving tourists in the process of craft making for educational tourism purposes.